Effect of internal geometry on the tensile strength of SLA-printed resin using a formlabs 3D printer - Roberth Marshall Ratlalan; Muh Farid Hidayat (Politeknik Negeri Lhokseumawe, 2025)
Stereolithography (SLA) is developing rapidly as a 3D printing technology in manufacturing high precision resin-based parts. This research investigates the influence of internal geometry on the tensile strength of samples printed with a Formlabs SLA printer using dental resin. Three types of internal geometries of solid control, triangular lattice, and honeycomb lattice were compared and evaluated. Samples were designed using Autodesk Inventor according to ASTM D638 standards and printed with symmetry axis dimensions of 5 mm and 10 mm and a consistent thickness of 5 mm. Tensile testing was conducted to analyze the influence of resin material type, internal geometry design, and dimensional parameters on their mechanical properties. The results showed that the solid internal geometry achieved the highest average tensile stress of 33.33 MPa meanwhile the triangular geometry with 5 mm configuration exhibited superior tensile performance compared to the honeycomb design.